Degerming carbon rod as well as preparation method and application thereof

By combining activated carbon particles and metal oxides with polyethylene binder in a specific particle size ratio, sterilization carbon rods are prepared, which solves the problem of insufficient filtration accuracy and sterilization rate of existing carbon rod filter media under low pressure drop and high flow rate, and achieves a highly efficient filtration effect.

CN121177845APending Publication Date: 2025-12-23XIAMEN BAILIN WATER PURIFICATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511532208.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2025-12-23

AI Technical Summary

Technical Problem

While existing carbon rod filter media can meet the requirements of low pressure drop and high flow rate, their filtration accuracy, sterilization rate, and removal rate of disinfection byproducts are relatively poor.

Method used

A sterilization carbon rod is prepared by mixing first activated carbon particles, second activated carbon particles and metal oxides with polyethylene binder in a specific particle size ratio and extruding them to form a three-dimensional network structure to improve filtration accuracy and sterilization rate.

Benefits of technology

Under conditions of low pressure drop and high flow rate, the filtration accuracy, sterilization rate and removal rate of disinfection byproducts are significantly improved, and the preparation method is simple and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of water purification filtering materials, and particularly relates to a degerming carbon rod as well as a preparation method and application thereof. The degerming carbon rod comprises first active carbon particles, second active carbon particles, a metal oxide, a polyethylene binder and a bacteriostatic agent. The ratio of the D50 particle size of the first activated carbon particles to the D50 particle size of the second activated carbon particles is (1.2-3.0): 1; the ratio of the D50 particle size of the second active carbon particles to the D50 particle size of the metal oxide is (1.2-5.0): 1; the D50 particle size of the metal oxide is 20-50 [mu] m; and the content of the metal oxide in the degerming carbon rod is 4-8wt%. The key point of the invention is to regulate and control the D50 particle size proportion and mass ratio of the first activated carbon particles, the second activated carbon particles and the metal oxide, so that the obtained carbon rod not only has low pressure drop and high flow rate, but also has high filtration precision, high sterilization rate and high disinfection byproduct removal rate.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of water purification filter materials, and particularly relates to a bacteria-removing carbon rod and a preparation method and application thereof. BACKGROUND

[0002] In recent years, as people's requirements for drinking water are getting higher and higher, the use frequency and demand of water purifiers in various working environments and living scenes are also increasing. Long-distance vehicles such as motor homes and civil aviation passenger planes are equipped with water tanks. Since the static water tank is prone to bacterial growth, the use of water purifiers places high demands on the microbial filtration capacity of filter core materials, and also has high requirements on the use space and flow rate.

[0003] As the core component of water purifiers, filter core materials can be mainly divided into activated carbon filter cores, ultrafiltration membrane filter cores, nanofiltration membrane filter cores, and reverse osmosis membrane filter cores. Among them, the reverse osmosis membrane with high filtration precision can remove microorganisms in water, but the cost of the reverse osmosis membrane is high, and usually a PP + activated carbon pretreatment is required in the front stage, resulting in a large equipment size, and in the use process, power supply and pressurization are required to provide filtration driving force, and beneficial minerals are also removed and waste water is generated, resulting in low resource utilization. Activated carbon is the first choice for high-performance filter core materials due to its low price, developed pore structure, good adsorption performance, and other physical and chemical performance characteristics. The utilization mode of activated carbon can be divided into powdered activated carbon and shaped activated carbon (carbon rod). Activated carbon rod is a cylindrical filter material made of activated carbon through hot sintering or extrusion molding, which can efficiently intercept particulate matter with a diameter of 0.5 μm or more in water, improve taste, and adsorb organic pollutants in water. Its operating conditions are simple, and the use cost is low, but its interception capacity for microorganisms with a diameter of less than 0.5 μm is limited, and the extrusion molding process does not have pore-forming properties due to the use of adhesives, and the pores of activated carbon are easily wrapped and lose effectiveness, which greatly reduces the adsorption effect. Therefore, it is crucial to develop a bacteria-removing carbon rod that meets the requirements of low pressure drop, high flow rate, and high filtration precision. SUMMARY

[0004] The present application aims to solve the problem of poor filtration precision, bacteria removal rate, and disinfection byproduct removal rate of existing carbon rod filter materials while meeting low pressure drop and high flow rate, and provides a new bacteria-removing carbon rod that can improve filtration precision and ensure low pressure drop, high flow rate, and significantly improved removal effect of bacteria, microorganisms, and disinfection byproducts.

[0005] In a first aspect, the present application provides a sterilization carbon rod. The sterilization carbon rod comprises first activated carbon particles, second activated carbon particles, metal oxide, polyethylene binder and bacteriostatic agent; the ratio of the D50 particle size of the first activated carbon particles to the D50 particle size of the second activated carbon particles is (1.2-3.0):1; the ratio of the D50 particle size of the second activated carbon particles to the D50 particle size of the metal oxide is (1.2-5.0):1; the D50 particle size of the metal oxide is 20-50 μm; the content of the metal oxide in the sterilization carbon rod is 4-8 wt%; the mass ratio of the first activated carbon particles, the second activated carbon particles and the metal oxide in the sterilization carbon rod is (2.5-15.0):(1.2-7.5):1.

[0006] In a preferred embodiment, the D50 particle size of the first activated carbon particles is 120-160 μm.

[0007] In a preferred embodiment, the D50 particle size of the second activated carbon particles is 60-100 μm.

[0008] In a preferred embodiment, the content of the first activated carbon particles in the sterilization carbon rod is 20-60 wt%; the content of the second activated carbon particles in the sterilization carbon rod is 10-30 wt%; the content of the binder in the sterilization carbon rod is 20-40 wt%; the content of the bacteriostatic agent in the sterilization carbon rod is 1-5 wt%.

[0009] In a preferred embodiment, the first activated carbon particles and the second activated carbon particles are each independently selected from any one or more of nut shell activated carbon, coconut shell activated carbon and coal-based activated carbon.

[0010] In a preferred embodiment, the bulk density of the first activated carbon particles is 0.45-0.60 g / mL and the iodine adsorption value is 1000-1200 mg / g.

[0011] In a preferred embodiment, the D10 particle size of the second activated carbon particles is 25-35 μm, the bulk density is 0.50-0.60 g / mL and the iodine adsorption value is 1000-1300 mg / g.

[0012] In a preferred embodiment, the metal oxide is selected from any one or more of aluminum oxide, zinc oxide, iron oxide, aluminum hydroxide, iron hydroxide, iron oxyhydroxide, aluminum silicate, manganese oxide, trimanganese tetraoxide and magnesium oxide.

[0013] In a preferred embodiment, the D50 particle size of the polyethylene binder is 60-110 μm and the weight average molecular weight is 20-17 million g / mol.

[0014] In a preferred embodiment, the length of the antibacterial charcoal rod is 60-263 mm, the inner diameter is 10-50 mm, and the outer diameter is 25-108 mm.

[0015] In a preferred embodiment, the weight of the antibacterial charcoal stick is 40~950g / PCS.

[0016] Secondly, the present invention provides a method for preparing the above-mentioned antibacterial charcoal rod. The preparation method includes the following steps: mixing first activated carbon particles, second activated carbon particles, metal oxide, polyethylene binder, and antibacterial agent, and extruding the resulting mixture to obtain the antibacterial charcoal rod.

[0017] In a preferred embodiment, the mixing process includes: firstly mixing the first activated carbon particles, the second activated carbon particles, the metal oxide, and the antibacterial agent, and then mixing the resulting first mixture with the polyethylene adhesive.

[0018] In a preferred embodiment, the conditions for the first mixing process include: a mixing speed of 1000~2000 r / min and a mixing time of 45~120 min.

[0019] In a preferred embodiment, the conditions for the second mixing process include: a mixing speed of 300-500 r / min and a mixing time of 30-60 min.

[0020] In a preferred embodiment, the screw speed during the extrusion molding process is 200~600 r / min.

[0021] In a preferred embodiment, the mixture undergoes three temperature zones from feeding to discharging during the extrusion molding process, wherein the first temperature zone is 120~160℃, the second temperature zone is 180~240℃, and the third temperature zone is 170~235℃.

[0022] Thirdly, the present invention also provides the application of the above-mentioned antibacterial charcoal rod in a water purifier.

[0023] Beneficial effects: The key to this invention lies in using metal oxides with specific D50 particle sizes and first activated carbon particles and second activated carbon particles with different D50 particle sizes as the main filter materials of the carbon rod. Based on this, the D50 particle size ratio and mass ratio of the three are adjusted, and then mixed with polyethylene binder and antibacterial agent and extruded to obtain a sterilizing carbon rod. Under the premise of low pressure drop and high flow rate, the sterilizing carbon rod has significantly improved filtration accuracy, sterilization rate and disinfection by-product removal rate. Moreover, the preparation method is simple and safe, with good economic value and application prospects. Detailed Implementation

[0024] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Furthermore, unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present invention.

[0025] The antibacterial charcoal rod provided by this invention comprises first activated carbon particles, second activated carbon particles, a metal oxide, a polyethylene binder, and an antibacterial agent. The ratio of the D50 particle size of the first activated carbon particles to the D50 particle size of the metal oxide is (1.2~3.0):1, such as 1.2:1, 1.5:1, 1.8:1, 2.0:1, 2.2:1, 2.5:1, 2.8:1, 3.0:1, or any value between them. The ratio of the D50 particle size of the second activated carbon particles to the D50 particle size of the metal oxide is (1.2~5.0):1, such as 1.2:1, 1.5:1, 1.8:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1, 5.0:1, or any value between them. The D50 particle size of the metal oxide is 20~50μm, such as 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any value between them. The content of metal oxide in the sterilizing charcoal rod is 4~8wt%, such as 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or any value between them. The mass ratio of the first activated carbon particles, the second activated carbon particles and the metal oxide in the sterilizing charcoal rod is (2.5~15.0):(1.2~7.5):1. Based on the mass of the metal oxide as 1 part by weight, the mass of the first activated carbon particles is 2.5~15.0 parts by weight, such as 2.5, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 12.0, 15.0 parts by weight or any value between them. The mass of the second activated carbon particles is 1.2 to 7.5 parts by weight, such as 1.2, 1.5, 1.8, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 7.5 parts by weight or any value between them, based on 1 part by weight of the metal oxide.

[0026] This invention achieves superior structural performance by controlling the D50 particle size and mass ratio of the first activated carbon particles, the second activated carbon particles, and the metal oxides. This mixture improves the filtration accuracy of the activated carbon rod while maintaining a low pressure drop, ensuring a high filtration flow rate. Furthermore, the addition of a polyethylene binder creates a robust three-dimensional network structure among the activated carbon, polyethylene binder, and metal oxides. This allows the activated carbon and metal oxides to effectively adsorb and intercept microorganisms and disinfection byproducts, thereby increasing the sterilization rate and the removal rate of disinfection byproducts.

[0027] In this invention, the D50 particle size of the first activated carbon particles is preferably 120~160μm, such as 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm or any value between them. The D50 particle size of the second activated carbon particles is preferably 60~100μm, such as 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm or any value between them.

[0028] In this invention, the content of the first activated carbon particles in the sterilizing charcoal rod is preferably 20-60 wt%, such as 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, or any value between them. The content of the second activated carbon particles in the sterilizing charcoal rod is preferably 10-30 wt%, such as 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, or any value between them. The content of the binder in the sterilizing charcoal rod is preferably 20-40 wt%, such as 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, or any value between them. The content of the antibacterial agent in the sterilizing charcoal rod is preferably 1-5 wt%, such as 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, or any value between them.

[0029] In this invention, there are no particular restrictions on the specific types and sources of the first and second activated carbon particles. Specific examples of each include, but are not limited to, any one or more of the following: fruit shell activated carbon, coconut shell activated carbon, and coal-based activated carbon.

[0030] In this invention, the bulk density of the first granular activated carbon is preferably 0.45~0.60 g / mL, such as 0.45 g / mL, 0.50 g / mL, 0.55 g / mL, 0.60 g / mL or any value between them; the iodine adsorption value is preferably 1000~1200 mg / g, such as 1000 mg / g, 1050 mg / g, 1100 mg / g, 1150 mg / g, 1200 mg / g or any value between them. The second granular activated carbon has a D10 particle size of 25~35μm, such as 25μm, 28μm, 30μm, 32μm, 35μm or any value between them; the bulk density is preferably 0.50~0.60g / mL, such as 0.50g / mL, 0.52g / mL, 0.55g / mL, 0.58g / mL, 0.60g / mL or any value between them; the iodine adsorption value is preferably 1000~1300mg / g, such as 1000mg / g, 1050mg / g, 1100mg / g, 1150mg / g, 1200mg / g, 1250mg / g, 1300mg / g or any value between them.

[0031] In this invention, specific examples of the metal oxide include, but are not limited to, any one or more of the following: aluminum oxide, zinc oxide, iron oxide, aluminum hydroxide, iron hydroxide, iron hydroxyl oxide, aluminum silicate, manganese oxide, manganese tetroxide, and magnesium oxide.

[0032] In this invention, the D50 particle size of the polyethylene binder is preferably 60-110 μm, such as 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm or any value between them. This is more conducive to the construction of a three-dimensional flow channel structure by polyethylene, first activated carbon particles, second activated carbon particles, and metal oxides, thereby improving the product flow rate and the retention effect on impurities such as particulate matter, bacteria, and disinfection byproducts in water. The weight-average molecular weight (Mn) of the polyethylene binder is preferably 2-17 million g / mol, such as 200 g / mol, 500 g / mol, 800 g / mol, 1000 g / mol, 1200 g / mol, 1500 g / mol, 1700 g / mol or any value between them.

[0033] In this invention, the length of the antibacterial charcoal rod is preferably 60-263 mm, such as 60 mm, 80 mm, 100 mm, 150 mm, 180 mm, 200 mm, 250 mm, 263 mm, or any value between them; the inner diameter is preferably 10-50 mm, such as 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, or any value between them; the outer diameter is preferably 25-108 mm, such as 25 mm, 50 mm, 75 mm, 100 mm, 108 mm, or any value between them. The weight of the antibacterial charcoal rod is preferably 40-950 g / PCS, such as 40 g / PCS, 50 g / PCS, 80 g / PCS, 100 g / PCS, 200 g / PCS, 500 g / PCS, 700 g / PCS, 950 g / PCS, or any value between them.

[0034] The present invention provides a method for preparing an antibacterial charcoal rod, comprising the following steps: mixing first activated carbon particles, second activated carbon particles, metal oxide, polyethylene binder, and antibacterial agent, and extruding the resulting mixture to obtain an antibacterial charcoal rod.

[0035] In this invention, the mixing process preferably includes: firstly, subjecting the first activated carbon particles, the second activated carbon particles, the metal oxide, and the antibacterial agent to a first mixing treatment; and then subjecting the resulting first mixture to a second mixing treatment with a polyethylene binder. The conditions for the first mixing treatment preferably include: a mixing speed of 1000~2000 r / min, such as 1000 r / min, 1200 r / min, 1500 r / min, 1800 r / min, 2000 r / min, or any value between these values; and a mixing time of 45~120 min, such as 45 min, 60 min, 75 min, 90 min, 105 min, 120 min, or any value between these values. The preferred conditions for the second mixing process include: a mixing speed of 300-500 r / min, such as 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min or any value between them; and a mixing time of 30-60 min, such as 30 min, 40 min, 50 min, 60 min or any value between them.

[0036] In this invention, the screw speed during the extrusion molding process is preferably 200~600 r / min, such as 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min or any value between them.

[0037] In this invention, the mixture undergoes three temperature zones from feeding to discharging during the extrusion molding process. The first temperature zone is preferably 120-160°C, such as 120°C, 130°C, 140°C, 150°C, 160°C, or any value between them. The second temperature zone is preferably 180-240°C, such as 180°C, 200°C, 220°C, 240°C, or any value between them. The third temperature zone is preferably 170-235°C, such as 170°C, 185°C, 200°C, 215°C, 235°C, or any value between them.

[0038] Furthermore, the term "D50 particle size" refers to the particle size corresponding to a sample when the cumulative particle size distribution percentage reaches 50%. The term "D10 particle size" refers to the particle size corresponding to a sample when the cumulative particle size distribution percentage reaches 10%. The terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as a particular limitation on the type, number, or nature of the technical features.

[0039] The present invention will be described in detail below through specific embodiments. These embodiments are intended to explain the invention and should not be construed as limiting it. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0040] Example 1 This embodiment illustrates the preparation of a sterilizing charcoal rod, and the specific process is as follows: Weigh out the following components by mass percentage: 43wt% of coarse coconut shell activated carbon particles with a D50 particle size of 140μm (bulk density of 0.51g / mL, iodine adsorption value of 1050mg / g), 20wt% of fine coconut shell activated carbon particles with a D50 particle size of 80μm (bulk density of 0.53g / mL, iodine adsorption value of 1050mg / g), 6wt% of alumina with a D50 particle size of 35μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene (Mn=10 million g / mol) with a D50 particle size of 70μm. Mix the coarse and fine coconut shell activated carbon particles, alumina, and silver-loaded antibacterial agent at a high-speed mixing rate of 1500 r / min for 60 min. After the above mixing is completed, polyethylene with a D50 particle size of 70μm (Mn=10 million g / mol) is added for further high-speed mixing at a mixing speed of 400 r / min for 30 min to obtain a mixture. This mixture is then fed into an extruder, where it passes through three temperature zones: 150℃, 230℃, and 220℃. The screw speed during extrusion is 400 r / min, resulting in a sterilizing charcoal rod with a length of 95 mm, an inner diameter of 25 mm, an outer diameter of 85 mm, and a basis weight of 350 g / pcS.

[0041] Example 2 This embodiment illustrates the preparation of a sterilizing charcoal rod, and the specific process is as follows: Weigh out the following components by mass percentage: 60wt% of coarse coconut shell activated carbon particles with a D50 particle size of 160μm (bulk density of 0.50g / mL, iodine adsorption value of 1050mg / g), 15wt% of fine coconut shell activated carbon particles with a D50 particle size of 60μm (bulk density of 0.54g / mL, iodine adsorption value of 1050mg / g), 4wt% of hydrated alumina with a D50 particle size of 50μm, 1wt% of silver-loaded antibacterial agent, and 20wt% of polyethylene (Mn=17 million g / mol) with a D50 particle size of 90μm. Mix the coarse and fine coconut shell activated carbon particles, alumina, and silver-loaded antibacterial agent at a high-speed mixing rate of 1000 r / min for 120 min. After the above mixing is completed, polyethylene with a D50 particle size of 90μm (Mn=17 million g / mol) is added for further high-speed mixing at a mixing speed of 500 r / min for 60 min to obtain a mixture. This mixture is then fed into an extruder, where it passes through three temperature zones: 150℃, 230℃, and 220℃. The screw speed during extrusion is 400 r / min, resulting in a sterilizing charcoal rod with a length of 95 mm, an inner diameter of 25 mm, an outer diameter of 85 mm, and a basis weight of 350 g / pcS.

[0042] Example 3 This embodiment illustrates the preparation of a sterilizing charcoal rod, and the specific process is as follows: Weigh out the following components by mass percentage: 25wt% of coarse coconut shell activated carbon particles with a D50 particle size of 120μm (bulk density 0.51g / mL, iodine adsorption value 1050mg / g), 30wt% of fine coconut shell activated carbon particles with a D50 particle size of 100μm (bulk density 0.52g / mL, iodine adsorption value 1050mg / g), 8wt% of iron oxide with a D50 particle size of 20μm, 2wt% of silver-loaded antibacterial agent, and 35wt% of polyethylene (Mn=4 million g / mol) with a D50 particle size of 110μm. Mix the coarse and fine coconut shell activated carbon particles, alumina, and silver-loaded antibacterial agent at a high-speed mixing rate of 2000 r / min for 60 min. After the above mixing is completed, polyethylene with a D50 particle size of 110μm (Mn=4 million g / mol) is added for further high-speed mixing at a mixing speed of 300 r / min for 30 min to obtain a mixture. This mixture is then fed into an extruder, where it passes through three temperature zones: 150℃, 230℃, and 220℃. The screw speed during extrusion is 400 r / min, resulting in a sterilizing charcoal rod with a length of 95 mm, an inner diameter of 25 mm, an outer diameter of 85 mm, and a basis weight of 350 g / pcS.

[0043] Example 4 This embodiment illustrates the preparation of a sterilizing charcoal rod, and the specific process is as follows: Weigh out the following components by mass percentage: 43wt% of coarse coconut shell activated carbon particles with a D50 particle size of 200μm (bulk density of 0.48g / mL, iodine adsorption value of 1050mg / g), 20wt% of fine coconut shell activated carbon particles with a D50 particle size of 120μm (bulk density of 0.51g / mL, iodine adsorption value of 1050mg / g), 6wt% of alumina with a D50 particle size of 35μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene (Mn=10 million g / mol) with a D50 particle size of 70μm. Mix the coarse coconut shell activated carbon particles, fine coconut shell activated carbon particles, and silver-loaded alumina antibacterial agent at a high-speed mixing rate of 1500 r / min for 60 min. After the above mixing is completed, polyethylene with a D50 particle size of 70μm (Mn=10 million g / mol) is added for further high-speed mixing at a mixing speed of 400 r / min for 30 min to obtain a mixture. This mixture is then fed into an extruder, where it passes through three temperature zones: 150℃, 230℃, and 220℃. The screw speed during extrusion is 400 r / min, resulting in a sterilizing charcoal rod with a length of 95 mm, an inner diameter of 25 mm, an outer diameter of 85 mm, and a basis weight of 350 g / pcS.

[0044] Example 5 This embodiment illustrates the preparation of a sterilizing charcoal rod, and the specific process is as follows: Weigh out the following components by mass percentage: 43wt% of coarse coconut shell activated carbon particles with a D50 particle size of 80μm (bulk density 0.53g / mL, iodine adsorption value 1050mg / g), 20wt% of fine coconut shell activated carbon particles with a D50 particle size of 45μm (bulk density 0.56g / mL, iodine adsorption value 1050mg / g), 6wt% of alumina with a D50 particle size of 35μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene (Mn=10 million g / mol) with a D50 particle size of 70μm. Mix the coarse coconut shell activated carbon particles, fine coconut shell activated carbon particles, and silver-loaded alumina antibacterial agent at a high-speed mixing rate of 1500 r / min for 60 min. After the above mixing is completed, polyethylene with a D50 particle size of 70μm (Mn=10 million g / mol) is added for further high-speed mixing at a mixing speed of 400 r / min for 30 min to obtain a mixture. This mixture is then fed into an extruder, where it passes through three temperature zones: 150℃, 230℃, and 220℃. The screw speed during extrusion is 400 r / min, resulting in a sterilizing charcoal rod with a length of 95 mm, an inner diameter of 25 mm, an outer diameter of 85 mm, and a basis weight of 350 g / pcS.

[0045] Comparative Example 1 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that 49wt% of coarse coconut shell activated carbon particles with a D50 particle size of 140μm, 20wt% of fine coconut shell activated carbon particles with a D50 particle size of 80μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene (Mn=10 million g / mol) with a D50 particle size of 70μm were weighed according to the mass percentage. All other conditions were the same as in Example 1, and the reference carbon rod was thus prepared.

[0046] Comparative Example 2 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that 63wt% of coconut shell activated carbon coarse particles with a D50 particle size of 140μm, 6wt% of alumina with a D50 particle size of 35μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene (Mn=10 million g / mol) with a D50 particle size of 70μm were weighed according to the mass percentage. All other conditions were the same as in Example 1, and the reference carbon rod was thus prepared.

[0047] Comparative Example 3 The RSA2 Purification Cartridge AC2 is a built-in carbon rod commonly used in commercially available commercial airliner filters. The carbon rod has an outer diameter, inner diameter, and length of 92mm*25mm*95mm, a rated throughput of 4000L, a flow rate of 3.78L / min, and is claimed to filter out 0.5~1μm particles, cysts, bacteria, and volatile organic compounds.

[0048] Comparative Example 4 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that the mass percentage of alumina with a D50 particle size of 35 μm was 2 wt%, and the other conditions were the same as in Example 1. The reference carbon rod was thus prepared.

[0049] Comparative Example 5 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that the mass percentage of alumina with a D50 particle size of 35 μm was 10 wt%, and the other conditions were the same as in Example 1. The reference carbon rod was thus prepared.

[0050] Comparative Example 6 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that 43wt% of coarse coconut shell activated carbon particles with a D50 particle size of 60μm (bulk density of 0.54g / mL, iodine adsorption value of 1050mg / g), 20wt% of fine coconut shell activated carbon particles with a D50 particle size of 20μm (bulk density of 0.56g / mL, iodine adsorption value of 1050mg / g), 6wt% of alumina with a D50 particle size of 5μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene with a D50 particle size of 70μm (Mn=10 million g / mol) were weighed according to the following mass percentages. All other conditions were the same as in Example 1. The reference carbon rod was thus prepared.

[0051] Comparative Example 7 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that 43wt% of coarse coconut shell activated carbon particles with a D50 particle size of 400μm (bulk density of 0.44g / mL, iodine adsorption value of 1050mg / g), 20wt% of fine coconut shell activated carbon particles with a D50 particle size of 200μm (bulk density of 0.49g / mL, iodine adsorption value of 1050mg / g), 6wt% of alumina with a D50 particle size of 100μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene with a D50 particle size of 1050μm (Mn=10 million g / mol) were weighed according to the following mass percentages. All other conditions were the same as in Example 1. The reference carbon rod was thus prepared.

[0052] Comparative Example 8 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The reference carbon rod was prepared according to the method of Example 1, except that 13wt% of coarse coconut shell activated carbon particles with a D50 particle size of 140μm (bulk density of 0.51g / mL, iodine adsorption value of 1050mg / g), 51wt% of fine coconut shell activated carbon particles with a D50 particle size of 80μm (bulk density of 0.53g / mL, iodine adsorption value of 1050mg / g), 6wt% of alumina with a D50 particle size of 35μm, 1wt% of silver-loaded antibacterial agent, and 30wt% of polyethylene with a D50 particle size of 70μm (Mn=10 million g / mol) were weighed according to the following mass percentages. All other conditions were the same as in Example 1. The reference carbon rod was thus prepared.

[0053] Comparative Example 9 This comparative example illustrates the preparation of a reference carbon rod, and the specific process is as follows: The following components were weighed according to mass percentage: 25wt% of coarse coconut shell activated carbon particles with a D50 particle size of 550μm (bulk density of 0.51g / mL, iodine adsorption value of 1050mg / g), 30wt% of fine coconut shell activated carbon particles with a D50 particle size of 130μm (bulk density of 0.52g / mL, iodine adsorption value of 1050mg / g), 8wt% of iron oxide with a D50 particle size of 20μm, 2wt% of silver-loaded antibacterial agent, and 35wt% of polyethylene (Mn=4 million g / mol) with a D50 particle size of 110μm. All other conditions were the same as in Example 1, and a reference carbon rod was prepared accordingly.

[0054] Test case (1) The pressure drop, flow rate and filtration accuracy of the carbon rods obtained in the above embodiments and comparative examples were tested according to the following methods. The results are shown in Table 1 below.

[0055] Pressure drop test: According to the rated flow rate of 3.78 L / min claimed by the carbon rod in Comparative Example 3, the inlet and outlet pressures of the empty fixture were tested at the rated flow rate. Then, the carbon rod was installed into the fixture, and the inlet and outlet pressures were tested at the rated flow rate.

[0056] Pressure drop = (Inlet water pressure with carbon rod - Outlet water pressure of fixture with carbon rod) - (Inlet water pressure of empty fixture - Outlet water pressure of empty fixture). Test water temperature 20±3℃.

[0057] Flow rate test: The carbon rods were loaded into the fixture, and 3 / 8-point pipes were used for the inlet and outlet. The flow rate of the carbon rods obtained in the example and comparative examples was tested under a water pressure of 30 PSI.

[0058] Filtration accuracy test: Prepare water spiked with particulate matter at a concentration of approximately 3,000,000 particles / mL (particle size of 0.5~1µm). Pass the spiked water through the carbon rod under test at a pressure of 60 PSI. Test the particulate matter concentration of the water sample before and after filtration, and calculate the particulate matter interception rate of the carbon rod to obtain the filtration accuracy.

[0059] Filtration accuracy = (1 - concentration of particulate matter after filtration / concentration of particulate matter before filtration) * 100.

[0060] Table 1

[0061] (2) The removal rates of E. coli and chloroform of the charcoal rods obtained in the above examples and comparative examples were tested according to the following methods. The results are shown in Table 2.

[0062] Escherichia coli removal rate test: The test strain was Escherichia coli 8099. The test bacteria were subcultured on nutrient agar slants every 24 hours, using cultures from the 3rd to 5th generation. The bacterial growth on the nutrient agar slants was washed off with a small amount of 0.85% sterile physiological saline, and then appropriately diluted with sterile physiological saline to obtain an initial concentration of (2 × 10⁻⁶). 6 ~2×10 7 A bacterial suspension of 2 × 10⁻¹ CFU / 100mL was prepared using dechlorinated tap water to achieve a concentration of (2 × 10⁻¹ CFU / 100mL). 5 ~4×10 5 CFU / 100mL of E. coli spiked solution was used. The colony count of E. coli was performed according to GB / T 5750.12-2006. The E. coli spiked solution was introduced, and the flow rate was controlled at 3.78 L / min for Examples 1-5 and Comparative Examples 1-7. Filtered water samples were taken at flow rates of 0 L, 1000 L, 2000 L, 3000 L, and 4000 L. The concentration of E. coli in the obtained filtered water samples was tested, and the removal rate was calculated.

[0063] Trichloromethane Removal Rate Test: General experimental water was prepared using RO water. Sodium chloride was used to adjust the TDS of the experimental water to 200-500 mg / L, and tannic acid chloride was used to adjust the TOC to >1 mg / L. The experimental water temperature was controlled at 20±2.5℃. Trichloromethane was added to the experimental water as a spike to prepare test water with a concentration of 300±30 μg / L. Two types of activated carbon rods (Example 2 and Comparative Example 3) were placed in a suitable testing fixture, connected to the testing machine, and the outlet flow rate was controlled at 3.78 L / min. After rinsing for 5 minutes, filtered water samples were taken at flow rates of 0 L, 1000 L, 2000 L, 3000 L, and 4000 L. The concentration of trichloromethane in the filtered water samples was tested using GC-MS. The trichloromethane removal rate was calculated based on the trichloromethane concentration in the test water.

[0064] Table 2

[0065] In Table 2, the " / " in Comparative Examples 3, 7, and 9 indicates that when the measured chloroform removal rate is already at a low level, there is no point in continuing the test. The " / " in Comparative Examples 5, 6, and 8 indicates that when the flow rate measured in Table 1 is much lower than 3.78 L / min, there is no need to test the chloroform removal rate due to its limited practical application significance.

[0066] Based on the results in Tables 1 and 2, it can be seen that, compared with Comparative Examples 1 to 9, the carbon rods provided in Examples 1 to 5 of the present invention can achieve high filtration accuracy, high E. coli removal rate, and high chloroform removal rate while meeting the requirement of flow rate ≥ 3L / min.

[0067] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.

Claims

1. A sterilizing charcoal rod, characterized in that, The sterilizing charcoal rod comprises first activated carbon particles, second activated carbon particles, metal oxide, polyethylene binder, and antibacterial agent; the ratio of the D50 particle size of the first activated carbon particles to that of the second activated carbon particles is (1.2~3.0):1; the ratio of the D50 particle size of the second activated carbon particles to that of the metal oxide is (1.2~5.0):1; the D50 particle size of the metal oxide is 20~50μm; the content of metal oxide in the sterilizing charcoal rod is 4~8wt%; the mass ratio of the first activated carbon particles, the second activated carbon particles, and the metal oxide in the sterilizing charcoal rod is (2.5~15.0):(1.2~7.5):

1.

2. The antibacterial charcoal rod according to claim 1, characterized in that, The D50 particle size of the first activated carbon particles is 120~160μm; Preferably, the D50 particle size of the second activated carbon particles is 60~100μm.

3. The antibacterial charcoal rod according to claim 1, characterized in that, The content of the first activated carbon particles in the sterilizing charcoal rod is 20-60 wt%; the content of the second activated carbon particles in the sterilizing charcoal rod is 10-30 wt%; the content of the binder in the sterilizing charcoal rod is 20-40 wt%; and the content of the antibacterial agent in the sterilizing charcoal rod is 1-5 wt%.

4. The antibacterial charcoal rod according to claim 1, characterized in that, The first activated carbon granules and the second activated carbon granules are each independently selected from any one or more of the following: fruit shell activated carbon, coconut shell activated carbon, and coal-based activated carbon. Preferably, the bulk density of the first granular activated carbon is 0.45~0.60 g / mL, and the iodine adsorption value is 1000~1200 mg / g; Preferably, the second granular activated carbon has a D10 particle size of 25~35μm, a bulk density of 0.50~0.60g / mL, and an iodine adsorption value of 1000~1300mg / g.

5. The antibacterial charcoal rod according to claim 1, characterized in that, The metal oxide is selected from any one or more of aluminum oxide, zinc oxide, iron oxide, aluminum hydroxide, iron hydroxide, iron hydroxyl oxide, aluminum silicate, manganese oxide, manganese tetroxide, and magnesium oxide. Preferably, the polyethylene adhesive has a D50 particle size of 60~110μm and a weight-average molecular weight of 200~1700 million g / mol.

6. The antibacterial charcoal rod according to claim 1, characterized in that, The length of the sterilization charcoal rod is 60~263mm, the inner diameter is 10~50mm, and the outer diameter is 25~108mm; Preferably, the weight of the antibacterial charcoal stick is 40~950g / PCS.

7. The method for preparing the antibacterial charcoal rod according to any one of claims 1 to 6, characterized in that, The preparation method includes the following steps: mixing first activated carbon particles, second activated carbon particles, metal oxide, polyethylene binder, and antibacterial agent, and extruding the resulting mixture to obtain antibacterial carbon rods.

8. The method for preparing the antibacterial charcoal rod according to claim 7, characterized in that, The mixing process includes: firstly mixing the first activated carbon particles, the second activated carbon particles, the metal oxide and the antibacterial agent, and then mixing the resulting first mixture with the polyethylene binder in a second mixing process. Preferably, the conditions for the first mixing process include: a mixing speed of 1000~2000 r / min and a mixing time of 45~120 min; Preferably, the conditions for the second mixing process include: a mixing speed of 300-500 r / min and a mixing time of 30-60 min.

9. The method for preparing the antibacterial charcoal rod according to claim 7, characterized in that, The screw speed during the extrusion molding process is 200~600 r / min; Preferably, during the extrusion molding process, the mixture is processed through three temperature zones from feeding to discharging, wherein the first temperature zone is 120~160℃, the second temperature zone is 180~240℃, and the third temperature zone is 170~235℃.

10. The application of the antibacterial charcoal rod according to any one of claims 1 to 6 in a water purifier.